The Development of Grade 11th Students Science Communication on Feedback Teaching Mixed with Virtual Classroom - Nakkrua, Thawanrat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The purposes of this research were to development of grade 11th students science communication to use feedback teaching mixed with virtual classroom. The samples were made up of 76 grade 11th students in Sciences-Mathematics program at the Demonstration school of Ramkhamhaeng university in their semester 1 Academic Year 2022 through a purposive Cluster random sampling. The tools of the research consisted of 1) virtual classroom, 2) feedback teaching for lesson plans under the topic digestion, 3) a test measuring the ability to science communication. Data was analyzed to find the means, the standard deviation (S.D.), and the paired samples t-test. The results showed that: In terms of the ability to science communication of grade 11th students undergoing the feedback teaching mixed with virtual classroom after was higher than before with statistically significance at the .05 level.